Russian-Ukraine Conflict and the Purpose of NATO: A Rethink - Ghulam Mujadid; Saba Kiran (National University of Modern Languages (NUML), Islamabad, 2024)
This article examines and contrasts Russia's and U.S.'s perspectives and actions throughout the conflict and attempts to determine why the conflict in Ukraine escalated into a global power struggle. Due to the abundance of biased and self-serving information about the Ukrainian situation, this article aims to objectively investigate some aspects of the actions and behaviours of the U.S. to expand NATO to Eastern European states; and Russia's bids to secure it near abroad. These conflicting strategic dynamics made their contributions to the situation. Since the data were gathered through books, journal papers, websites, and periodicals, the study is a desk study. It is qualitative because it draws on various sources to analyze this problem and comprehend the opposing viewpoints. Russia and the U.S. are sponsoring rival militias to strategically dominate the Black Sea Region for their economic gains. To keep one another from achieving hegemonic dominance in the Black Sea region, both governments worked in their self-interest to strengthen their respective positions and undercut those of their rivals. How the Ukraine conflict evolved would have been different had the two great powers not been involved in the ways they did.